Patient-level meta-analysis of efficacy and hypoglycaemia in people with type 2 diabetes initiating insulin glargine 100 U/mL or neutral protamine Hagedorn insulin analysed according to concomitant oral antidiabetes therapy. (February 2017) - Owens, David R.; Traylor, Louise; Mullins, Peter; Landgraf, Wolfgang
Highlights: Insulin glargine 100 U/mL achieved similar glycaemic control as NPH insulin. Overall and nocturnal hypoglycaemia risk was lower with insulin glargine 100 U/mL. These outcomes were observed regardless of concomitant oral antidiabetes drug. Weight gain and insulin doses were higher with insulin glargine 100 U/mL. Concomitant MET + SU led to better glycaemic control but higher hypoglycaemic risk. Abstract: Aims: Evaluate efficacy and hypoglycaemia according to concomitant oral antidiabetes drug (OAD) in people with type 2 diabetes initiating insulin glargine 100 U/mL (Gla-100) or neutral protamine Hagedorn (NPH) insulin once daily. Methods: Four studies (target fasting plasma glucose [FPG] ⩽100 mg/dL [⩽5.6 mmol/L]; duration ⩾24 weeks) were included. Standardised data from 2091 subjects (Gla-100, n = 1024; NPH insulin, n = 1067) were analysed. Endpoints included glycated haemoglobin (HbA1c) and FPG change, glycaemic target achievement, hypoglycaemia, weight change, and insulin dose. Results: Mean HbA1c and FPG reductions were similar with Gla-100 and NPH insulin regardless of concomitant OAD ( P = 0.184 and P = 0.553, respectively) and similar proportions of subjects achieved HbA1c <7.0% ( P = 0.603). There was a trend for more subjects treated with Gla-100 achieving FPG ⩽100 mg/dL versus NPH insulin (relative risk [RR] 1.09 [95% confidence interval (CI) 0.97–1.23]; P = 0.135). Plasma glucose confirmed (<70 mg/dL) overall and nocturnal hypoglycaemia incidences and rates were lower with Gla-100 versus NPH insulin (overall RR 0.93 [95% CI 0.87–1.00]; P = 0.041; nocturnal RR 0.73 [95% CI 0.65–0.83]; P < 0.001). After 24 weeks, weight gain and insulin doses were higher with Gla-100 versus NPH insulin (2.7 kg vs 2.3 kg, P = 0.009 and 0.42 U/kg vs 0.39 U/kg; P = 0.003, respectively). Insulin doses were higher when either insulin was added to sulfonylurea alone. Conclusions: Pooled results from treat-to-target trials in insulin-naïve people with type 2 diabetes demonstrate a significantly lower overall and nocturnal hypoglycaemia risk across different plasma glucose definitions with Gla-100 versus NPH insulin at similar glycaemic control. OAD therapy co-administered with Gla-100 or NPH insulin impacts glycaemic control and overall nocturnal hypoglycaemia risk.